Potensi Daya Tarik Wisata Green Talao Park di Nagari Ulakan Kabupaten Padang Pariaman - Annisa Elfiani; Kurnia Illahi Manvi (Departemen Pariwisata Universitas Negeri Padang, 2022)
This study aims to find out how the Potential of Green Talao Park Tourism Attraction in Nagari Ulakan Padang Pariaman Regency is with four indicators of tourist attraction, namely: a) attraction, b) accessibilities, c) amenities, d) ancillary services. This type of research is descriptive qualitative survey method. The sources of information in this study used purposive sampling, totaling nine people, namely two people from the Padang Pariaman Regency Tourism Office, one Wali Nagari, one person from the Head of the Pesisir Ulakan Bumnag, one Pokdarwis Green Talao Park, two local people and two visitors. Based on the research results, the authors found several potential tourist attractions for Green Talao Park, namely: 1) the Green Talao Park attraction has the potential for natural tourist attractions, namely having unspoiled natural beauty such as the stretch of Talao forest which has a 1.8 km tracking path with the flora and fauna in it as well as beautiful beach views with sunsets. In addition to natural tourism, Green Talao Park also provides artificial tourism such as tree houses, gazebos, water rides, and a love pier. 2) accessibilities with good road conditions, but the road from the entrance gate to the parking lot is still narrow, there is no special public transportation to get there, the distance to Green Talao Park is 44 km from the center of Padang City and 16 km from the International Airport. 3) amenities, namely the availability of toilets, prayer rooms, places to eat and drink, trash cans, but there is no souvenir shop. 4) there are no ATMs for ancillary services, no health facilities, but there is a puskesmas that is close to Green Talao Park and already has an information center and monitoring post.